Auditory Narrative: Keroncong Music in the Construction of Cinematic Meaning (Cinematology: Journal Anthology of Film and Television Studies, 2026)
This article discusses the role of keroncong music as an auditory narrative element that shapes cinematic meaning in Indonesian contemporary film. Music in film functions not merely as an emotional backdrop but also as a bearer of meaning, symbolism, and cultural identity. The focus of this analysis is a scene from “Losmen Bu Broto: The Series” (Episode 3, minute 27:15), which features keroncong music both diegetically and non-diegetically. Using a qualitative-descriptive approach, this study examines how the musical structure of keroncong, its rhythm, harmony, timbre, and nostalgic nuance interacts with the film’s visual and narrative elements. The findings show that keroncong serves as a temporal and emotional marker that strengthens characterization and conveys cultural depth within Indonesian cinema.